Deteksi Dini Status Gizi Menggunakan IMT/U - Wahyuni Sammeng; Khartini Kaluku; Santi Aprilian Lestaluhu (STIKES Marendeng Majene, 2026)
Early detection of nutritional status in preschool-aged children is a crucial step in preventing malnutrition and its long-term effects on child growth and development. Assessing the nutritional status of kindergarten children is part of the national standards regarding the growth and development of children aged 4 – 6 years. This activity In June 2026, the community service team from Poltekkes Kemenkes Maluku conducted this activity. by the community service team from Poltekkes Kemenkes Maluku in June 2026. The program took place at Imam Asy-Syafi’i Kindergarten in Ambon, with 13 students present during the event. The method employed involved growth monitoring through anthropometric measurements using the Body Mass Index-for-Age (BMI-for-Age) index. The results indicated that 61.5% of the students a normal nutritional status, while 38.5% were classified as having an nutritional status, while 38.5% were classified as having excess nutritional status. Key benefits of the activity included the use of standard measurement tools such as digital scales and the application of standardized measurement procedures. Furthermore, the teachers gained a deeper understanding of nutritional status, enabling them to conduct such assessments independently in the future.